THE SYNERGY OF DPRD AND GORONTALO PROVINCE GOVERNMENT IN THE MODEL COLLABORATIVE GOVERNANCE - Espin Tulie; Asna Aneta, Yanti Aneta, Ismet Sulila (Adisam Publisher, 2025)
This study aims to explore the synergy between the DPRD and the provincial government in order to create effective governance using a collaborative governance approach. This study focuses on four key elements, namely initial conditions, institutional design, leadership, and collaboration processes. Qualitative methods are applied with data collection techniques in the form of in-depth interviews, field observations, documentation studies, and focus group discussions. The results of the study indicate that collaboration between the DPRD and the provincial government is often colored by differences in priorities. The DPRD tends to focus on constituent aspirations, while the provincial government emphasizes macro-scale development strategies. Institutional designs, such as public consultation forums and Musrenbang , although designed to support collaboration, still require optimization to be more effective. Inclusive and communicative leadership plays an important role in building harmonious working relationships, while less responsive leadership can be an obstacle. This study recommends aligning visions, strengthening institutional mechanisms, developing collaborative leadership styles, and using technology to increase transparency and efficiency. These findings are expected to contribute to improving regional governance in a more inclusive and sustainable manner.